PRODUCTION OF FURNITURE ELEMENTS WITH PARTICLEBOARD CUTTING WASTE CORE - Angelski, Dimitar; Atanasova, Krasimira; Angelova, Vanesa (Innovation in Woodworking Industry and Engineering design, 2024)
The scarcity of natural resources and the generation of waste without adequate disposal are worldwide concerns related to the linear production model. The present study is part of a research project to create a technology for the utilization of laminated particleboard cutting waste in furniture element production. A layer of waste details was laminated on both sides with High Pressure Laminate (HPL) with a thickness of 0.8 mm. Polyvinyl acetate adhesive was used for lamination. The influence of the lamination process conditions and the arrangement scheme of the core details on the appearance, bending strength, and processing features in the subsequent technological phases of the manufacturing process has been established.